Peran Krusial Hakim, Hukum, Al-Mahkum Fih dan Al-Mahkum Alaih dalam Penegakan Hukum Islam - Salsa Luthfiah Rezki; Fahrial S; Safitri Aulia Zalsalnabila; Kurniati Kurniati (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2025)
The enforcement of Islamic law in Indonesia is still marked by various complexities, one of which is the unclear role of Judges, Law, Al-Mahkum Fih (object of law), and Al-Mahkum Alaih (subject of law). This study aims to analyze the crucial role of these four elements in the enforcement of Islamic law. Judges have a central role in the enforcement of Islamic law. They are tasked with trying cases based on Islamic law and ensuring justice for all parties. The role of judges is strengthened by a competent mastery of Usul Fiqh and an understanding of the developing social context. Islamic law used in law enforcement in Indonesia is sourced from the Qur'an and Hadith. The application of Islamic law must consider the local social and cultural context. A legal anthropology approach can be used to understand and accommodate local values ​​in the application of Islamic law. Al-Mahkum Fih is the act or action of mukallaf regulated in Islamic law. Al-Mahkum Alaih is an individual or legal entity that is the subject of Islamic law. Effective enforcement of Islamic law requires clear identification of Al-Mahkum Fih and Al-Mahkum Alaih.